Treatment initiation decisions in newly diagnosed epilepsy–A longitudinal cohort study. (4th February 2020) - Sharma, Sameer; Chen, Zhibin; Rychkova, Maria; Dunne, John; Lee, Judy; Kalilani, Linda; Lawn, Nicholas; Kwan, Patrick
Abstract: Objective: To examine the factors and reasons influencing treatment initiation decisions in patients with newly diagnosed epilepsy. Methods: We assessed antiseizure medication initiation decisions in adults with newly diagnosed epilepsy seen at first seizure clinics in Western Australia between 1999 and 2016 and followed to 2018. Results: Of 610 patients (median age 40 years, 61.0% male), 426 (69.8%) were diagnosed after two or more seizures and 184 (30.2%) after a single seizure with risk factors for recurrence. Treatment was commenced in 427 patients (70.0%) at diagnosis, 112 (18.4%) during follow‐up, mostly after further seizures, whereas 71 (11.6%) remained untreated at last follow‐up. Elders (≥65 years, odds ratio [OR] = 3.06, 95% confidence interval [CI]: 1.62‐5.80), more seizures (OR = 3.48, 95% CI: 2.03‐5.96), and epileptogenic lesions on neuroimaging (OR = 2.15, 95% CI: 1.26‐3.68) had a higher likelihood of treatment at diagnosis. Patients with less than one seizure per year within the preceding year (OR = 0.40, 95% CI: 0.21‐0.73) and of higher socioeconomic status (OR = 0.985, 95% CI: 0.977‐0.994) were less likely to be treated. For 93 patients (15.2%), treatment was not recommended at diagnosis, most commonly because only a single seizure had occurred. Ninety patients (14.8%) declined recommended treatment, mostly because they were unconvinced of the need for treatment or the diagnosis. Significance: Thirty percent of adults with newly diagnosed epilepsy were not immediately treated. Treatment initiation in this real‐world cohort was influenced by age, number of seizures prior to diagnosis, imaging findings, patient preferences, and socioeconomic status.